2022
DOI: 10.5194/hess-26-2997-2022
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vegetation water dynamics on the ASCAT backscatter–incidence angle relationship in the Amazon

Abstract: Abstract. Microwave observations are sensitive to plant water content and could therefore provide essential information on biomass and plant water status in ecological and agricultural applications. The combined data record of the C-band scatterometers on the European Remote-Sensing Satellites (ERS)-1/2, the Metop (Meteorological Operational satellite) series, and the planned Metop Second Generation satellites will span over 40 years, which would provide a long-term perspective on the role of vegetation in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…For coniferous forest, a high correlation (R 2 ) was achieved between the Sentinel-1 SAR backscatter and the ET products of up to 0.86 (full signal) and up to 0.99 (filtered signal with only the seasonality component). Additionally, an influence of overpass direction on the degree of the correlation with an increase from an R 2 of around 0.5 (descending, morning) to around 0.9 (ascending, evening) was shown, suggesting that the daily change of vegetation water storage due to canopy transpiration is visible, even though not fully decrypted at the moment [70]. Moreover, differences of backscatter variability were shown between dry and wet years, further endorsing this outcome.…”
Section: Discussionmentioning
confidence: 64%
“…For coniferous forest, a high correlation (R 2 ) was achieved between the Sentinel-1 SAR backscatter and the ET products of up to 0.86 (full signal) and up to 0.99 (filtered signal with only the seasonality component). Additionally, an influence of overpass direction on the degree of the correlation with an increase from an R 2 of around 0.5 (descending, morning) to around 0.9 (ascending, evening) was shown, suggesting that the daily change of vegetation water storage due to canopy transpiration is visible, even though not fully decrypted at the moment [70]. Moreover, differences of backscatter variability were shown between dry and wet years, further endorsing this outcome.…”
Section: Discussionmentioning
confidence: 64%
“…When backscatter is obtained at multiple incidence angles, one can quantify the relationship between incidence angle and backscatter, which is strongly driven by changes in vegetation, with an increase in vegetation leading to a less steep slope (Wagner et al, 1999b;Naeimi et al, 2009). The slope has been used to monitor phenology and vegetation water dynamics and to retrieve VOD (Vreugdenhil et al, 2017;Steele-Dunne et al, 2019;Petchiappan et al, 2022). In addition, when cross-polarized backscatter is measured, this can be used to quantify vegetation dynamics (Toan et al, 1992;Paloscia et al, 1998;Saatchi et al, 2013;Khabbazan et al, 2019).…”
Section: Fundamental Concepts In Microwave Remote Sensingmentioning
confidence: 99%
“…Coarse resolution data from radiometers and scatterometers has mainly been used to monitor drought impact on forests. Studies have demonstrated the potential of vegetation parameters such as VOD to monitor drought impact on vegetation, particularly on forests (Konings et al, 2021), such as the Amazon in 2005, 2010 and 2015 (Saatchi et al, 2013;Liu et al, 2018;Petchiappan et al, 2022), and on tree mortality (Rao et al, 2019). Over croplands and pastures only very few studies have been performed using coarse resolution data, mostly passive microwave-based VOD (Buitink et al, 2020;Afshar et al, 2021;Likith et al, 2022) or the active microwave-based slope from the backscatter incidence angle relationship (Schroeder et al, 2016;Vreugdenhil et al, 2017;Steele-Dunne et al, 2019;Petchiappan et al, 2022).…”
Section: Vegetation Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also use the slope of the backscatter incidence angle relation of Metop ASCAT (Vreugdenhil et al, 2016). This radar observable is sensitive to vegetation water content and fresh biomass (Steele-Dunne et al, 2019;Petchiappan et al, 2022). Additionally, we use two ground-based vegetation datasets: Normalized Microwave Reflection Index (NMRI) measurements obtained from GPS reflectometry and sapflow observations from the SAPFLUXNET network.…”
mentioning
confidence: 99%